Pattern and presentation of acute abdomen in a Nigerian teaching hospital - Agboola, John Owoade (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Abdominal pain of sudden onset is the hallmark of most non-traumatic emergency surgical presentations. This presents a scenario of urgency to the young surgeon who has to determine which of a myriad of disease conditions the patient is presenting with. Such a physician has to rely on experience and a sound knowledge of the local aetiological spectrum in making a clinical diagnosis. OBJECTIVE: To determine the epidemiology and aetiological spectrum of diseases presenting as acute abdomen in the adult population at the hospital surgical emergency unit. PATIENTS AND METHODS: Two hundred and seventy-six patients presenting at the University of Ilorin Teaching Hospital emergency unit and managed by the general surgeons between 1(st) of May 2009 and 30(th) of April 2010 were recruited and followed-up throughout the period of admission. The biodata and clinical information inclusive of diagnosis, investigations, treatment modality and outcome were entered in a structured questioner. Standardised treatment was given to all patients and difficulties encountered in their management were also noted. The data collected was evaluated using SPSS16. RESULTS: Acute abdomen constituted 9.6% of total surgical emergency admissions with patients aged 16-45 years constituting 78.3%. The commonest cause of acute abdomen was appendicitis (30.3%) followed by intestinal obstruction (27.9%), perforated typhoid ileitis 14.9% and peptic ulcer disease (7.6%), respectively. CONCLUSION: The result from the study is similar to what has been reported in other tropical settings with inflammatory lesions being the major problem. There is also a rising incidence of post-operative adhesions and gradual decline in incidence of obstructed hernia.